Obstetric and perinatal risks after the use of donor sperm: A systematic review and meta-analysis. (July 2022) - Pohjonen, E.-M.; Söderström-Anttila, V.; Bergh, C.; Loft, A.; Magnusson, Å.; Pinborg, A.; Oldereid, N.B.; Petzold, M.; Romundstad, L.B.; Laivuori, H.
Abstract: Donor sperm is widely used in infertility treatments. The purpose of the study was to investigate, whether use of donor sperm in intrauterine insemination (IUI) or in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) treatments affect maternal and perinatal risks compared with spontaneously conceived pregnancies or use of partner sperm in IUI, IVF or ICSI. We provide a systematic review and meta-analyses on the most clinically relevant obstetric and perinatal outcomes after use of donor sperm compared with partner sperm: hypertensive disorders of pregnancy, preeclampsia, low birth weight, and preterm birth. Our meta-analyses showed an increased risk for preeclampsia (pooled adjusted odds ratio (aOR) 1.77, 95% CI 1.26–2.48) and hypertensive disorders of pregnancy (pooled aOR 1.55, 95%, CI 1.20–2.00) in pregnancies resulting from IUI with donor sperm compared with IUI with partner sperm. No increased risk was seen for low birth weight or preterm birth after the use of donor sperm in IUI compared with the use of partner sperm in IUI. Subgroup analysis for singletons only did not change these results. The meta-analysis on low birth weight showed a lower risk after in IVF with donor sperm compared with IVF with partner sperm (pooled aOR 0.89, 95% CI 0.83–0.94). For hypertensive disorders of pregnancy, preeclampsia and preterm birth, no difference was found between IVF with donor sperm vs. partner sperm. Patients need to be informed about the moderately increased risk of hypertensive disorders of pregnancy and preeclampsia in pregnancies after IUI with donor sperm.